The Dynamics of Local Government Crisis Communication in the Post-Truth Era: A Case Study of The Land and Building Tax Increase Controversy in Cirebon City - Heru Sulistiyo; Kamal Alamsyah (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
This study analyzes the dynamics of public policy communication in the post-truth era, using the case study of the Land and Building Tax (PBB) increase controversy in Cirebon City in 2024. This study aims to identify government communication strategies, explore the role of media and disinformation, and uncover new findings related to the adaptation of government communication amidst the crisis. A qualitative-descriptive approach was used, using critical discourse analysis techniques for policy documents, online media coverage, and official government statements. Key findings indicate that the government's communication strategy was initially reactive and tended to use a one-way model (Public Information and Two-Way Asymmetrical), which was ineffective in dampening public sentiment. However, public pressure forced the government to reactively shift to a two-way symmetrical communication model, which was realized through the revocation of the Mayoral Regulation (Perwali). This shift occurred not as a proactive choice, but rather as a defensive response to the crisis triggered by the post-truth environment. This report recommends that the government adopt a more proactive and adaptive communication model from the outset to prevent crisis escalation and build sustainable public trust.